Beyond the Conventional Wisdom: Rural Development As If Australia's Rural People and Communities Really Mattered - Jonathan P. Sher; Katrina Rowe Sher (Journal of Research in Rural Education, 1994)
When we were approached by Australia's Commonwealth Department of Primary Industries and Energy (DPIE) in June 1993 and asked to write a report on rural Australia, the officials there did not have in mind the document now in your hands. They asked us to prepare a paper that would focus on strategies for advancing "rural development" through education and entrepreneurship. While they encouraged us to establish the broader context-to sketch the whole puzzle into which the education and entrepreneurship pieces could be placed-this was assumed to be a minor part of the assignment.